Long-term mental health care for people with severe mental disorders – the importance of workplace rehabilitation - Boardman, J. (Die Psychiatrie, 2013)
Work and meaningful activity have historically played a key role in rehabilitation services for people with severe mental health problems and continues to do so today. People with long-term and severe mental disorders have low rates of employment. In the last 30 years the increasing emphasis on raising the sights of mental health services to focus on personal recovery and the importance given to social justice and to combating social exclusion has led to a focus on gaining open employment. Individual Placement and Support (IPS) has emerged as an important and evidence-based scheme for getting people with severe mental health problems into open employment. Despite the strong and consistent evidence for the effectiveness of IPS, these schemes are not widely implemented. This paper summarises the background to, and research on, IPS and possible barriers to its wider implementation.
Keywords: Supported employment; individual placement and support; employment; mental health